The development of oxygenators in extra corporeal circulation - Mimikos Stylianos; Stroggili Evlabia; Karapanagiotidis Georgios (Ellīniko Periodiko tīs Nosīleutikīs Epistīmīs, 2020)
The objective of this paper is to present one of the most important components of the extracorporeal circulation circuit, the oxygenator. In addition, the manufacture materials, the function and superiority of modern oxygenators are presented in order to stress their advantages over the older types. The future of oxygenators and the tendency to develop small intravascular artificial lungs are also discussed. A bibliographic study of the history and first reports of extracorporeal blood oxygenation has been performed in an attempt to describe the function of these initial oxygenators and to analyze the disadvantages which led to the development and to the exclusive of the membrane oxygenators. Since the establishment of the current knowledge that the artificial membrane of the modern oxygenators is the best material to oxygenate blood and remove carbon dioxide during extracorporeal circulation, further research concerning the oxygenator’s membrane was necessary to solve particular problems, such as plasma leak. Technologic advantages in the oxygenator’s membrane made possible the safe use of the oxygenator for 28 days in the extracorporeal membrane oxygenation (ECMO) circuits. The different materials used for the construction of the oxygenators are discussed with details. The incorporation in the oxygenator of additional devices, such as the heat exchanger, the arterial filter and blood reservoir to develop one compact construction is considered to be one more upgrade of the oxygenator’s technology. Accidents and safety precautions of the oxygenators are also discussed especially that of the thrombosis of the device. The necessity for more detailed and accurate monitoring of the oxygenator in real time during cardiac surgery is discussed. The latter holistic approach to the operation of the oxygenator and of the components which incorporate in the device offers specific advantages, while modification of the surface in contact with the blood ameliorates the inflammatory response.